T-cell immunology in sarcoidosis: Disruption of a delicate balance between helper and regulatory T-cells. Issue 5 (September 2016) - Broos, Caroline E.; Hendriks, Rudi W.; Kool, Mirjam
Abstract : Purpose of review: Although the aetiology of sarcoidosis is not yet completely understood, immunological changes within the T-cell compartment are characteristic for an exaggerated antigen-driven immune response. In this review, we describe the most recent findings on T-cell subset responses and regulation in sarcoidosis. We discuss how future immunological research can advance the field to unravel pathobiological mechanisms of this intriguingly complex disease. Recent findings: Research into the field of T-cell plasticity has recently challenged the long-held T helper type 1 (Th1) paradigm in sarcoidosis and striking parallels with autoimmune disorders and common variable immunodeficiency were recognized. For instance, it was demonstrated that Th17.1-cells rather than Th1-cells are responsible for the exaggerated IFN-γ production in pulmonary sarcoidosis. Furthermore, impaired regulatory T-cell function and alterations within the expression of co-inhibitory receptors that control T-cell responses, such as PD-1, CTLA-4 and BTNL2, raise new questions regarding T-cell regulation in pulmonary sarcoidosis. Summary: It becomes increasingly clear that Th17(.1)-cells and regulatory T-cells are key players in sarcoidosis T-cell immunology. New findings on plasticity and co-inhibitory receptor expression by these subsets help build a more comprehensive model for T-cell regulation in sarcoidosis and will finally shed light on the potential of new treatment modalities.